2020
DOI: 10.1038/s41366-020-0612-9
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, cardiometabolic risk factors and effect modification of physical activity in children and adolescents: pooled data from 12 international studies

Abstract: Objectives Low and high birth weight is associated with higher levels of cardiometabolic risk factors and adiposity in children and adolescents, and increases the risk of cardiovascular diseases, obesity, and early mortality later in life. Moderate-to-vigorous physical activity (MVPA) is associated with lower cardiometabolic risk factors and may mitigate the detrimental consequences of high or low birth weight. Thus, we examined whether MVPA modified the associations between birth weight and cardiometabolic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…To achieve health benefits, it is recommended that children and adolescents aged 5–17 years participate in an average of 60 min or more moderate-to-vigorous physical activity (MVPA) per day [ 12 ]. Although the benefits of PA have been well identified, physical inactivity remains a major public health problem [ 13 , 14 ]. The Healthy Active Kids South Africa (HAKSA) 2018 report indicated that 50% of children are not meeting the recommended average of 60 min of MVPA per day [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve health benefits, it is recommended that children and adolescents aged 5–17 years participate in an average of 60 min or more moderate-to-vigorous physical activity (MVPA) per day [ 12 ]. Although the benefits of PA have been well identified, physical inactivity remains a major public health problem [ 13 , 14 ]. The Healthy Active Kids South Africa (HAKSA) 2018 report indicated that 50% of children are not meeting the recommended average of 60 min of MVPA per day [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanism(s) by which changes in circadian rhythm could affect fetal metabolism remain unknown, but maternal blue‐light exposure may result in alterations in maternal glucose tolerance 8 . This may lead to alterations in placental nutrient and glucose transport, which have detrimental outcomes on fetal growth 45,49 . The associations of maternal blue‐light exposure with infant birthweight may also be explained by endocrinological events caused by blue‐light exposure that may re‐entrain the uterus’ circadian rhythm and lead to a disturbed rhythm in utero .…”
Section: Discussionmentioning
confidence: 99%
“…Although low and high birthweight is a risk factor for obesity and chronic metabolic disorders later in life, 48 , 49 no studies have investigated the relationship between maternal blue‐light exposure and infant birthweight. Most studies were performed in nonpregnant subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mothers reported the number of times their 7 years‐old child participated in MVPA outside of school hours in a usual week. The question has previously been compared with accelerometer‐assessed physical activity and is considered useful for ranking children according to level of physical activity 29 . For the joint association analyses, we categorized the variables into 0–2 times/week, 3–4 times/week, and ≥5 times/week.…”
Section: Methodsmentioning
confidence: 99%